Free radical scavenging activity of taro (Colocasia esculenta (L.) Schott) varieties with varying flesh color - Vasquez, Erlinda A.; Contero, Precila D.; Ferraren, Dilberto O. (Annals of Tropical Research, 2020)
Corms of five taro varieties namely two NSIC-registered varieties, VG-1 (Kalpao) and VG-2 (Iniito), and three farmer’s variety, PRG 322 (Chowking), PRG 381 (Pandaga), and PRG 380 (Salot), were evaluated for antioxidant activity using 1, 1-diphenyl-2 picrylhydrazyl (DPPH) assay before and after cooking. The purple-fleshed varieties PRG 322, PRG 380 and VG-2 showed higher antioxidant activity than the yellow- and cream-fleshed varieties, The monomeric anthocyanin contents of PRG 380 and VG-1 PRG 322 and VG-2, which showed the highest free radical scavenging activity were measured using the pH differential method. The free-radical scavenging activity of the five taro varieties ranged from 134 to 154TEμm g-1 when raw and 127 to 147TEμm g-1 when cooked with the highest activity in raw PRG 322 followed by raw PRG 380 and VG-2. Cooked PRG 381 and VG-1 showed the lowest activity, Cooking reduced the activity by 4.5-10.2% with PRG 380 showing the highest reduction rate while the other four varieties did not vary significantly from 4.5-5.9%. Decreased in antioxidant activity can be due to the degradation and leaching out of antioxidant compounds during steamed cooking.